2011
DOI: 10.1073/pnas.1100977108
|View full text |Cite
|
Sign up to set email alerts
|

Paul trapping of charged particles in aqueous solution

Abstract: We experimentally demonstrate the feasibility of an aqueous Paul trap using a proof-of-principle planar device. Radio frequency voltages are used to generate an alternating focusing/defocusing potential well in two orthogonal directions. Individual charged particles are dynamically confined into nanometer scale in space. Compared with conventional Paul traps working in frictionless vacuum, the aqueous environment associated with damping forces and thermally induced fluctuations (Brownian noise) exerts a fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 30 publications
0
61
0
Order By: Relevance
“…Recently, Guan et al [1, 2] have showed the feasibility of an aqueous , radio-frequency (rf, AC) quadrupole micro-trap for localization and control of charged micro-particles. This is a remarkable extension of the applicability of the quadrupole Paul micro-trap [3, 4] in addition to its conventional applications in mass spectrometry [5], quantum information processing [6, 7], microdynamical sensors [8], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Guan et al [1, 2] have showed the feasibility of an aqueous , radio-frequency (rf, AC) quadrupole micro-trap for localization and control of charged micro-particles. This is a remarkable extension of the applicability of the quadrupole Paul micro-trap [3, 4] in addition to its conventional applications in mass spectrometry [5], quantum information processing [6, 7], microdynamical sensors [8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that typical biomolecules (e.g. proteins) are stable in water and have a considerable amount of charge [9, 10], this novel aqueous quadrupole micro-trap is an excellent candidate for localization and manipulation of their motion in a confinement region of space [1, 2, 11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, trapping multiple cells (or particles) for shorter durations could be achieved by alternating the polarity of the compressional and extensional flow axes, analogous to implementing a Paul trap in aqueous solution. 55 In addition, trapping techniques with higher temporal resolution may require decoupling image acquisition with centroid detection by implementing hardware trapping for improved feedback latency as reported in methods such as optical 27 and electrophoretic techniques. 38 …”
Section: Discussionmentioning
confidence: 99%
“…However, confinement and fine-scale manipulation of macromolecules and nanoparticles remains a significant challenge. Currently, particle trapping methods based on acoustic [1][2][3][4] , electrokinetic [5][6][7][8][9][10][11][12][13][14][15] , magnetic [16][17][18] , and optical [19][20][21][22][23][24][25][26][27][28] fields are utilized, but these methods are limited to trapping particles with specific material properties and bulky micron-scale dimensions. [29][30][31] Recently, we developed a new flow-based confinement method that enables 2-D manipulation of single micro and nanoscale particles suspended in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%